(untitled) (Indian Journal of Animal Production and Management, 2018)
This research work was carried out to evaluate the bio-gas production potential of four different substrates viz. ruminant dung (cattle and goat) and non-ruminant excreta (pig and poultry). The bio-gas production potential of non-ruminants excreta was found to be significantly higher than ruminant excreta due to less fibre content, presence of undigested fermentable carbohydrates (volatile solids) and reduced nitrogen content. The bio-gas production potential of pig excreta was found to be significantly (P<0.01) higher than goat followed by poultry and cattle.